Novel phosphate glasses for bone regeneration applications - Burling, Luke Donald (2006)
Phosphate glass with additions of sodium, magnesium and/or calcium were investigated for their potential to be used as the reinforcing phase in a completely degradable long fibre composite. Glasses were prepared from phosphate salts as opposed to oxides and melted under air in platinum/gold crucibles. The effect of cation addition on the material properties and biocompatibility was investigated. Glasses were characterised using a number of complimentary techniques, including: XRD, XPS, DSC, IR and EDX. The findings from these techniques were used to explain the observed thermal and dissolution properties.